HYPERTENSION AND PREHYPERTENSION AMONG APPARENTLY HEALTHY MEDICAL STUDENTS: AN ASSESSMENT OF MODIFIABLE CARDIOVASCULAR RISKS FACTORS (The Research of Medical Science Review, 2025)
Background of the Study Hypertension has emerged as a major public health issue and is among the top risk factors for mortality in low- and middle-income nationsPrehypertension serves as a precursor to hypertension and, on its own, has a significant positive linear correlation with the morbidity and mortality related to cardiovascular disease (CVD) Methodology Students from many medical institutions participated in a cross-sectional research. A non-probability convenience sampling technique was used to choose a sample.Blood pressure and anthropometric measures were performed. Fisher exact tests or chi-square tests were used to compare categorical variables. Result Among 386 participants 36 % were female and 64 % were males..there is a higher male ratio in elevated blood pressures that is 23.1% male and 5.7% females are lie in the category of prehypertension followed 4.1% male suffered from Grade 1 hypertension. Conclusion Hypertension and cardiovascular risk factors are significant among university students in Karachi, Pakistan. Physical inactivity and salt consumption are key risk factors in this demographic.